2012
DOI: 10.1103/physrevlett.108.191802
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Reactor Electron Antineutrinos Disappearance in the RENO Experiment

Abstract: The RENO experiment has observed the disappearance of reactor electron antineutrinos, consistent with neutrino oscillations, with a significance of 4.9 standard deviations. Antineutrinos from six 2.8  GW(th) reactors at the Yonggwang Nuclear Power Plant in Korea, are detected by two identical detectors located at 294 and 1383 m, respectively, from the reactor array center. In the 229 d data-taking period between 11 August 2011 and 26 March 2012, the far (near) detector observed 17102 (154088) electron antineut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
1,432
2
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,766 publications
(1,490 citation statements)
references
References 28 publications
51
1,432
2
5
Order By: Relevance
“…In this work we illustrate our points, without any loss of generality, by resorting to normal hierarchy of the neutrino mass spectrum and setting the lowest neutrino mass eigenvalue to zero. Furthermore, using the observed central values of the various lepton mixing angles, the elements of the neutrino mass matrix M ν can be found by using the equation [47,48], the left-hand side of equation (3.16) is completely known, at least in orders of magnitude. The actual mass matrix thus constructed has some elements at least one order of magnitude smaller than the others, thus suggesting texture zeros.…”
Section: Jhep02(2014)060mentioning
confidence: 99%
“…In this work we illustrate our points, without any loss of generality, by resorting to normal hierarchy of the neutrino mass spectrum and setting the lowest neutrino mass eigenvalue to zero. Furthermore, using the observed central values of the various lepton mixing angles, the elements of the neutrino mass matrix M ν can be found by using the equation [47,48], the left-hand side of equation (3.16) is completely known, at least in orders of magnitude. The actual mass matrix thus constructed has some elements at least one order of magnitude smaller than the others, thus suggesting texture zeros.…”
Section: Jhep02(2014)060mentioning
confidence: 99%
“…Measurements from the Sudbury Neutrino Observatory a few years later, in combination with SK data, revealed that neutrino oscillation was responsible for the apparent deficit of electron neutrinos produced in the Sun [2]. In the most recent major advance, the T2K experiment [3,4] and reactor experiments [5][6][7][8] have established that all three neutrino mass states are mixtures of all three-flavor states, which allows the possibility of CP violation in neutrino oscillation. This paper describes our most recent measurements of neutrino oscillation including our first results from analyses that combine measurements of muon neutrino disappearance and electron neutrino appearance.…”
Section: Introductionmentioning
confidence: 99%
“…The T2K experiment has confirmed the neutrino oscillation in the ν µ → ν e appearance events [1], which provide us the new information of the CP violation of the lepton sector by combining the data of reactor experiments [2][3][4][5]. Therefore, the detailed study of the neutrino mixing including the CP violating phase gives us clues to reach the flavor theory [6]- [28].…”
Section: Introductionmentioning
confidence: 99%